Oxford/AstraZeneca COVID-19 vaccine trial: adverse patient event reports - Shakir, Saad (Henry Stewart Talks, 2020)
Mode of action of the Oxford/AstraZeneca DNA vaccine, Two potential adverse events reported in patients enrolled in the vaccine’s phase 3 trial, Steps undertaken to determine possible causality between the adverse events and the vaccine, Differences between RNA and DNA vaccine properties and mechanism of action, Current status of the trial, Please note that since the recording of this interview it was determined that "The serious adverse events observed during the trial in these study groups were judged to be unrelated to the study vaccines and occurred at frequencies expected for these conditions in the general population. None of the participants included in this report had any suspected unexpected serious adverse reactions." (Ramasamy et al., The Lancet, November 18, 2020, https://www.thelancet.com/journals/lancet/article/PIIS0140-6736(20)32466-1/fulltext).